Optical Fiber Sensor to Monitor Physical Measurands for Civil Applications - Dhingra, Ishant (My University, 2018)
In the past few years, the fiber bragg grating sensors have offered a great potential for a wide range of applications in many fields. Many bragg grating sensors such as fiber bragg grating sensors, long-period fiber gratings sensors, tilted fiber bragg gratings sensors, chirped fiber bragg gratings sensors have shown high sensitivity, stability, immunity to electromagnetic interference and environmental ruggedness. There has been a noticeable contribution of these bragg gratings-based components in different fields such as biomedical applications for brain pressure monitoring, military applications for guided missiles temperature measurement and civil applications for structural health monitoring. The bragg grating sensors consist of periodic gratings having different grating refractive index. The objective of this dissertation is to design and analyse various optical fiber sensors based on bragg gratings. The transmission characteristics and propagation of waves have been studied with the help of electromagnetic frequency domain to find the wavelength shifts. The study to design fiber bragg grating sensor was carried out with the help of software. The effect of strain on various infrastructure is also analyzed. Firstly, an optical fiber bragg grating sensor is designed in Comsol software. The performance of fiber bragg grating sensor is enhanced by selecting appropriate material for its fabrication. By introducing desirable refractive index, writing large number of gratings selecting, appropriate dimensions result in wavelength variation at desired value. These modifications are done to achieve enhanced sensitivity and better sensing operations. Further, we investigated that the proposed fiber bragg grating sensor can also be used to analyze the effect of strain on metal rods (corroded or non-corroded) at different temperature values. The wavelength shift is analyzed to monitor the strength of metal rods. The graphs for different transmission wavelengths revealed that this sensor would be applicable for monitoring the strength of metal pipes used in massive structure and the parameters that effect its strength.
Keywords: Sensors; Fiber Bragg Gratings; Strain; civil